Standardizing and monitoring the delivery of surgical interventions in randomized clinical trials. Issue 10 (27th July 2016) - Blencowe, N. S.; Mills, N.; Cook, J. A.; Donovan, J. L.; Rogers, C. A.; Whiting, P.; Blazeby, J. M.
Abstract : Background: The complexity of surgical interventions has major implications for the design of RCTs. Trials need to consider how and whether to standardize interventions so that, if successful, they can be implemented in practice. Although guidance exists for standardizing non‐pharmaceutical interventions in RCTs, their application to surgery is unclear. This study reports new methods for standardizing the delivery of surgical interventions in RCTs. Methods: Descriptions of 160 surgical interventions in existing trial reports and protocols were identified. Initially, ten reports were scrutinized in detail using a modified framework approach for the analysis of qualitative data, which informed the development of a preliminary typology. The typology was amended with iterative sequential application to all interventions. Further testing was undertaken within ongoing multicentre RCTs. Results: The typology has three parts. Initially, the overall technical purpose of the intervention is described (exploration, resection and/or reconstruction) in order to establish its constituent components and steps. This detailed description of the intervention is then used to establish whether and how each component and step should be standardized, and the standards documented within the trial protocol. Finally, the typology provides a framework for monitoring the agreed intervention standards during the RCT. Pilot testing within ongoing RCTs enabled standardization of the interventions to be agreed, and case report forms developed to capture deviations from these standards. Conclusion: The typology provides a framework for use during trial design to standardize the delivery of surgical interventions and document these details within protocols. Application of this typology to future RCTs may clarify details of the interventions under evaluation and help successful interventions to be implemented. Abstract : Design a perfect study